Artificial intelligence and global security future trends, threats and considerations - Masakowski, Yvonne (Emerald Publishing, 2020)
Artificial Intelligence and Global Security: Future Trends, Threats and Considerations brings a much-needed perspective on the impact of the integration of Artificial Intelligence (AI) technologies in military affairs. Experts forecast that AI will shape future military operations in ways that will revolutionize warfare. That is why there is an urgent need to consider the potential ethical and moral consequences related to enabling AI to make decisions that will shape the future world. This book masterfully presents a vision of a future that is replete with integrated networks of Artificial Intelligence that are designed to both defend and attack nations. Artificial Intelligence and Global Security: Future Trends, Threats and Considerations has rendered a major service to those interested in the impact of Artificial Intelligence technologies and its contribution to the evolution and revolution in military warfare. It will also explore questions such as: What are the implications of AI for the individual, for personal identity, for society, and for global security? And examine the impact of AI on Just War Theory, as well as the perspectives and consequences for the integration of AI in our daily lives and society.